Back Cover Image: Volume 3 Issue 2. Issue 2 (28th June 2022) - Shen, Chenglong; Jiang, Tianci; Lou, Qing; Zhao, Wenbo; Lv, Chaofan; Zheng, Guangsong; Liu, Hangrui; Li, Pengfei; Dai, Lingling; Liu, Kaikai; Zang, Jinhao; Wang, Feng; et al.
Abstract : Back cover image : Highly biocompatible and self‐illuminating carbon nanogels (CNGs) with dual ability of ROS imaging and PDT have been designed with self‐assembled chemiluminescent carbonized polymer dots (CPDs). Different CPDs have been derived from biomass materials and exhibit polymer‐like property, enabling their ability of self‐assembling into CNGs through the hydrophilic and hydrophobic interaction. With efficient deep‐red/near‐infrared (NIR) CL emission and distinctive PDT capacity, H2 O2 ‐driven water‐soluble chemiluminescent carbon nanogels are further designed by assembling the polymeric conjugate and CL donors. Mechanistically, ROS generated in the inflammatory sites can trigger the chemically initiated electron exchange luminescence between the CPDs and intermediate, enabling in vitro and in vivo CL imaging. Meanwhile, the production of such as 1 O2, OH and –O2 from the chemiluminescent CNGs under the self‐illumination can efficiently induce the apoptosis of tumor cell thus inhibit the tumor growth, resulting in cancer therapy. (DOI: 10.1002/smm2.1099 )